2007
DOI: 10.1007/s10553-007-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of catalytic reforming with continuous regeneration of the catalyst

Abstract: The results of a pilot run of the LF-35/21-1000 reforming unit with continuous regeneration of the catalyst at LUKOIL -Nizhegorodnefteorgsintez Co. are reported. It was found that all of the blocks and units operate in accordance with the project requirements. Dependences that correlate the quality of reforming naphtha with its yield and the yield of hydrogen-containing gas and power consumption with the output of the unit were obtained.Catalytic reforming naphtha occupies a leading position (52.8 vol. %) in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…The simulation results delivered by our model are compared to values for the Universal Oil Products (UOP) CCR pilot plant reported by Rassadin et al 27 The obtained simulation operating indices are in good agreement with the reported information reported in Table 3. Solutions for the other process variables obtained by the CCR model simulation are presented in Table 4.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The simulation results delivered by our model are compared to values for the Universal Oil Products (UOP) CCR pilot plant reported by Rassadin et al 27 The obtained simulation operating indices are in good agreement with the reported information reported in Table 3. Solutions for the other process variables obtained by the CCR model simulation are presented in Table 4.…”
Section: Resultssupporting
confidence: 83%
“…The catalyst is progressively coked as it moves through the reactors. The catalyst leaving each reactor enters the next one, and the total residence time of the catalyst in the system typically ranges between 2 and 7 days. , The catalyst leaving the last reactor is sent to the continuous catalyst regeneration units. The coked catalyst undergoes a sequence of steps involving controlled coke combustion, oxychlorination, and calcinations to restore catalyst activity and metal redispersion.…”
Section: Ccr Reformer Modelmentioning
confidence: 99%
“…Nakon pronalaženja minimuma "Random Walk" metodom, a s obzirom da ona ne daje egzaktnu Rezultati dobijeni simulacijom modela za kontinualno-regenerativni proces upoređeni su sa vrednostima za kontinualno-regenerativno pilot postrojenja [101] (Tabela 4.3).…”
Section: Slika 48 Uprošćeni šEmatski Prikaz Optimizacije Procesa Priunclassified
“…Upoređivanjem vrednosti operativnih indeksa dobijenih simulacijom i eksperimentalnih vrednosti [101], može se zaključiti da se rezultati simulacije dobro slažu sa eksperimentalnim. Vrednosti ostalih procesnih veličina dobijenih simulacijom, prikazani su u Tabeli 4.4.…”
Section: Slika 48 Uprošćeni šEmatski Prikaz Optimizacije Procesa Priunclassified